Massive post-traumatic neglicted diaphragmatic hernia revealed by necrotizing pancreatitis, A case report according scare guidelines. (August 2021) - Siham, Elmir; Mohammed, Noumairi; Rachid, Jabi; Mohammed, Bouziane; Maryam, Fourtassi; Ahmed Amine, El Oumri
Highlights: Atypical chest presentation of acute pancreatitis consisting of a post-traumatic of less than 10 cases reported in the literature. We describe a very exceptional complication of diaphragmatic rupture. We propose to take into consideration diaphragmatic involvement in any patient suffering from abdominal trauma.